Microfluidic cell culture chip and array - Gu, Jingjing. (2009)
In this project, the microfludic cell culture chip and array has been designed and fabricated by combining microfabrication and microfluidic technologies with the optimization of the biochip material, cell substrate material and the individual cell culture chamber structure. Typical cell culture manipulations have been realized on the microfluidic biochip, including the cell loading, attaching, growing as well as trypsinization process. Major problems have been overcome. The cells can grow circularly for 2 week without the morphology changing and proliferation rate reducing. As such, many traditional biological assays, for instance, immunofluorescence assay, can be carried out in a much smaller volume but with a higher throughput and higher accuracy. The cell culture array chip has then been used for the dynamic measurements of living cell’s RI through on-chip immersion refractometry which serves as an indicator of cellular proliferation rate. To further eliminate the undesirable osmotic pressure, an improved indicator-based immersion refractometry has been developed. This method can be utilized for real time monitoring and measurement of cellular physical properties to detect the pathological changes of cells. It is therefore of high potential for cancer cell analysis.